Obesity Mediates Apoptosis and Extracellular Matrix Metabolic Imbalances via MAPK Pathway Activation in Intervertebral Disk Degeneration - Zhang, Xuyang; Chen, Jian; Huang, Bao; Wang, Jiasheng; Shan, Zhi; Liu, Junhui; Chen, Yilei; Li, Shengyun; Fan, Shunwu; Zhao, Fengdong (Frontiers in Physiology, 2019)
Obesity may promote intervertebral disc degeneration (IDD) by non-mechanical means, by influencing levels of free fatty acids which could impair cell metabolism. This study aims to establish metabolic factors in obesity-related IDD independent of mechanical loading. In clinical study, we retrospectively reviewed 128 volunteers (73 males, 55 females, aged 29-88 years) and compared their grades of disc degeneration with obesity-related factors such as body weight, BMI, and serum lipid levels. Clinically, the IDD group showed increased age, BMI and serum triglyceride. Triglyceride was a significant risk factor for IDD even after correction for BMI and age (P=0.007). In obesity animal model, rats were fed a high-fat diet (HFD) in order to study its effects on disc metabolism and apoptosis. HFD rats had significantly higher serum levels of lipids, including triglyceride and nonesterified fatty acid, and showed significantly decreased markers of anabolism, increased catabolism and apoptosis in disc. Finally, rat nucleus pulposus (NP) cells were stimulated in vitro with a fatty acid (palmitic acid, PA) to gauge its effects on cell metabolism and apoptosis. Cell culture studies showed that NP cells exposed to PA showed increased apoptosis for activation of caspase 3, 7, 9, and PARP, which was primarily via the MAPK signal pathway, especially ERK pathway. In conclusion, hypertriglyceridemia can lead to IDD, independently of age and BMI. Hypertriglyceridemia appears to mediate disc cell apoptosis and matrix catabolism primarily via the ERK pathway.